Nowe rozwiązania w stosunkach handlowych EWG z krajami rozwijającymi się - Nędzyński, Jacek (Wydział Prawa i Administracji UAM, 1977)
The last few years make a period of an unusual economic and political activity of the developing countries tending to change their economic status in the world. Many international conferences trying to work out an universal help conception for the Third World have reflected this tendency. The signature of the „co-operation agreement" which has been subscribed in Lomé, February the 28th, 1975 by the EEC and by 46 African, Caribbean and Pacific countries, is being willingly presented by EEG authorities as a model of exemplary relations between prospering and developing countries. The Lomé agreement should really bring advantage to the above-mentioned developing countries (all the more so as almost all commercial restrictions have been one-sidedly repeald and so as the export incomes stabilization system has been introduced), especially in the moment when the universal help programs for the Third World cannot reach to be realized. On the other hand, many resolutions of this agreement are arousing reservations. Almost all the „Black Africa" and some other developing countries will find in the EEC businesses a consequence of the agreement. For the EEC, the agreement is one more step continuing the traditional colonial bonds and the policy of expansion in the Third World. The agreement will render difficult the relations between socialist countries and that countries which have signed it. In this situation, the socialist countries must tend to work out new forms of co-operation, especially in industrial and technological spheres. It seems that some Third World countries would do better if tried to update their own economy instead of searching for the EEC help in order to attain their speed-up economic progress.
New Solutions in the Economic Relations Between the EEC and Developing Countries